Therapeutic Ion-Releasing Bioactive Glass Ionomer Cements with Improved Mechanical Strength and Radiopacity - Fuchs, Maximilian; Gentleman, Eileen; Shahid, Saroash; Hill, Robert G.; Brauer, Delia S. (Frontiers in Materials, 2015)
Bioactive glasses (BG) are used to regenerate bone, as they degrade and release therapeutic ions. Glass ionomer cements (GIC) are used in dentistry, can be delivered by injection and set in situ by a reaction between an acid-degradable glass and a polymeric acid. Our aim was to combine the advantages of BG and GIC, and we investigated the use of alkali-free BG (SiO2-CaO-CaF2-MgO) with 0 to 50% of calcium replaced by strontium, as the beneficial effects of strontium on bone formation are well documented. When mixing BG and poly(vinyl phosphonic-co-acrylic acid), ions were released fast (up to 90% within 15 minutes at pH 1), which resulted in GIC setting, as followed by infrared spectroscopy. GIC mixed well and set to hard cements (compressive strength up to 35 MPa), staying hard when in contact with aqueous solution. This is in contrast to GIC prepared with poly(acrylic acid), which were shown previously to become soft in contact with water. Strontium release from GIC increased linearly with strontium for calcium substitution, allowing for tailoring of strontium release depending on clinical requirements. Furthermore, strontium substitution increased GIC radiopacity. GIC passed ISO10993 cytotoxicity test, making them promising candidates for use as injectable bone cements.